The Effect of PAD, DAU and DAK on Poverty Rates in Java - Astuti, Suryani Yuli; Basyah, Muhammad Ali; Niswah, Farokhah Muzayinatun (International Journal of Science, Technology & Management, 2021)
This study was made to determine the extent of the influence of Regional Original Income (PAD), General Allocation Funds (DAU) and Special Allocation Funds (DAK) on poverty through Regional Expenditures in Bitung City. Based on the time series data for 2016-2018 and processed based on the multiple regression analysis method for testing the path analysis used, it can be seen that the relationship between PAD, DAU, DAK and poverty rates on the island of Java. The results showed that the province of West Java on PAD, DAU and DAK had a partial effect on poverty rates and PAD, DAU and DAK had a simultaneous effect on poverty rates. Central Java Province on PAD has a negative effect on poverty rates, DAU and DAK have a partial effect on poverty rates and PAD, DAU and DAK have a simultaneous effect on poverty rates. DIY Province, although PAD has a negative effect on poverty rates, DAU has an effect on poverty and DAK has no partial effect on poverty rates and PAD, DAU and DAK have a simultaneous effect on poverty rates. East Java Province, Partially PAD has no effect on poverty rates, DAU has no effect on poverty rates and DAK has no effect on poverty rates and the influence of PAD, DAU and DAK simultaneously affects poverty rates.